2014
DOI: 10.1186/1475-2875-13-20
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Pf HRP2 versus Pf-pLDH antigen detection by malaria rapid diagnostic tests in hospitalized children in a seasonal hyperendemic malaria transmission area in Burkina Faso

Abstract: BackgroundIn most sub-Saharan African countries malaria rapid diagnostic tests (RDTs) are now used for the diagnosis of malaria. Most RDTs used detect Plasmodium falciparum histidine-rich protein-2 (PfHRP2), though P. falciparum-specific parasite lactate dehydrogenase (Pf-pLDH)-detecting RDTs may have advantages over PfHRP2-detecting RDTs. Only few data are available on the use of RDTs in severe illness and the present study compared Pf-pLDH to PfHRP2-detection.MethodsHospitalized children aged one month to 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 39 publications
8
53
1
1
Order By: Relevance
“…Published WHO product evaluation on different malaria RDT products submitted for testing has shown that targeting P. falciparum HRP2 has the highest and most consistent detection rate [16]. However, this conflicts with other findings in which HRP2-based RDTs have shown a lower performance value than products using pLDH for detecting P. falciparum , as the pLDH capture system is not affected by a possible ‘prozone’ effect, parasite antigen polymorphisms or gene deletions [37-41]. In Myanmar, a study comparing a commonly used RDT utilizing HRP2 and pan pLDH compared with microscopy demonstrated P. vivax and P. malariae were detected to a far lesser extent (lower sensitivity, NPV, and NLR) than P. falciparum [42].…”
Section: Discussionmentioning
confidence: 99%
“…Published WHO product evaluation on different malaria RDT products submitted for testing has shown that targeting P. falciparum HRP2 has the highest and most consistent detection rate [16]. However, this conflicts with other findings in which HRP2-based RDTs have shown a lower performance value than products using pLDH for detecting P. falciparum , as the pLDH capture system is not affected by a possible ‘prozone’ effect, parasite antigen polymorphisms or gene deletions [37-41]. In Myanmar, a study comparing a commonly used RDT utilizing HRP2 and pan pLDH compared with microscopy demonstrated P. vivax and P. malariae were detected to a far lesser extent (lower sensitivity, NPV, and NLR) than P. falciparum [42].…”
Section: Discussionmentioning
confidence: 99%
“…One important factor is the variability within the parasite antigens detected by the RDTs, which includes presence or absence of the target epitopes and variations in the number of epitopes in a particular parasite isolate (Lee et al, 2006; Lee et al, 2012; Maltha et al, 2014; Talman et al, 2007). Genetic diversity may be particularly important for PfHRP2-based RDTs, since most of the RDTs are based on this antigen (Mouatcho and Goldring, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of this test varies from 71 to 100% according to literature. 18,20,26 Labor was managed by midwives and residents, using a partograph, as recommended by the World Health Organization.…”
Section: Methodsmentioning
confidence: 99%
“…Positive *RDTm n (%) Negative*RDTm n (%) P-value (15)(16)(17)(18)(19)(20) Table 1 shows the characteristics of women included into the study. The (15-20) age group, single (marital status), lack of financial resources, <4 antenatal visits, the nonuse of mosquito bed nets, the absence of iron prophylaxis and a previous history of malaria crisis during the current pregnancy were associated with malaria infection at the onset of labor.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation